2019
DOI: 10.1002/ece3.5436
|View full text |Cite
|
Sign up to set email alerts
|

Length polymorphisms at two candidate genes explain variation of migratory behaviors in blackpoll warblers (Setophaga striata)

Abstract: Migratory behaviors such as the timing and duration of migration are genetically inherited and can be under strong natural selection, yet we still know very little about the specific genes or molecular pathways that control these behaviors. Studies in candidate genes Clock and Adcyap1 have revealed that both of these loci can be significantly correlated with migratory behaviors in birds, though observed relationships appear to vary across species. We investigated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 75 publications
3
23
3
Order By: Relevance
“…Our findings of a genetic driver of migratory life history variation align with recent findings from salmonids (Hecht et al, 2013;Kelson et al, 2019;Pearse et al, 2019) and other vertebrate taxa (mammals -Berg et al, 2019;McDevitt et al, 2009;birds -Delmore et al, 2016;Ralston et al, 2019).…”
Section: Accepted Articlesupporting
confidence: 89%
“…Our findings of a genetic driver of migratory life history variation align with recent findings from salmonids (Hecht et al, 2013;Kelson et al, 2019;Pearse et al, 2019) and other vertebrate taxa (mammals -Berg et al, 2019;McDevitt et al, 2009;birds -Delmore et al, 2016;Ralston et al, 2019).…”
Section: Accepted Articlesupporting
confidence: 89%
“…Although the observed relationships between candidate genes CLOCK and ADCYAP1 and migratory behavior in birds appear to vary across species, previous studies revealed that both loci can be signi cantly correlated with a variety of distinct phenotypes in long distance migratory birds [2,81]. For example, in blackpoll warblers (Setophaga striata), a Neotropical-Nearctic migrant, minimum ADCYAP1 allele length was signi cantly and negatively associated with spring departure date and positively associated with fall arrival date at the wintering grounds [5]. Longer ADCYAP1 alleles seem to be associated with earlier spring arrival dates [6], earlier postnatal dispersal and plumage morph [82], greater migratory restlessness [1,4].…”
Section: Discussionmentioning
confidence: 98%
“…Speci c genes or gene regions, and polymorphisms at candidate genes, may explain phenotypic variance in many aspects of migratory behavior [2]. Previous studies have pointed out that ADCYAP1 and CLOCK gene expression are essential to the control of migratory behavior but there is controversy about whether allele size is associated with migratory activity, spring and fall migratory duration, and arrival and departure dates [1,[3][4][5]. In addition, it has been suggested that potential interaction between ADCYAP1, wing morphology and sex predict spring migration arrival in blackcap populations [6] and that both ADCYAP1 and CLOCK gene alleles increase in size with breeding latitude in trans-Saharan migratory birds [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Blackpoll Warblers are an excellent model species to explore strategies during spring migration because of their extensive breeding range spanning the continent in the boreal forest, their long-distance migration, and their clear sexual dichromatism. As a result of their breeding range, the distance traveled from their South American wintering grounds by Blackpoll Warblers breeding furthest west is twice that of those breeding in the eastern parts of their range (Morris et al 2016, DeLuca et al 2019. Despite these potentially interesting differences in migration patterns across the range of this species, the majority of studies have focused on a single site (e.g., Morris et al 1994, Dunn 2002, Bonter et al 2007, Holzschuh and Deutschlander 2016 until recently (DeLuca et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their breeding range, the distance traveled from their South American wintering grounds by Blackpoll Warblers breeding furthest west is twice that of those breeding in the eastern parts of their range (Morris et al 2016, DeLuca et al 2019. Despite these potentially interesting differences in migration patterns across the range of this species, the majority of studies have focused on a single site (e.g., Morris et al 1994, Dunn 2002, Bonter et al 2007, Holzschuh and Deutschlander 2016 until recently (DeLuca et al 2019). Rosenberg et al (2016) have suggested that Blackpoll Warbler populations are declining at one of the highest rates of all North American birds.…”
Section: Introductionmentioning
confidence: 99%